Two layer segmentation for handling pathological motion in degraded post production media - KOKARAM, ANIL CHRISTOPHER (IEEE, 2004)
The paper presents a mechanism for dealing with incorrect motion estimation in degraded post production image sequences. This tends to be caused by pathological motion (a combination of motion blur, complex foreground motion, shadows, etc.). We describe a method for estimating where such regions are likely to occur by segmenting sequences into foreground and background motion. We show it is possible to produce a conservative matte of which regions in a sequence are foreground, and that blotch (dirt and sparkle defects) detection can be adapted accordingly in such areas.
PUBLISHED
Keywords: Electronic & Electrical Engineering